2022
DOI: 10.1109/access.2022.3174595
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Application in Terahertz Technology: A Review on Achievements and Future Challenges

Abstract: Terahertz (THz) radiation (0.1~10 THz) shows great potential in agricultural products detection, biomedical, and security inspection in recent years. Machine learning methods are widely used to support the user demand of higher efficiency and high prediction accuracy. The technological and key challenges of machine learning methods are for THz spectroscopy and image data preprocessing, reconstruction algorithms, and qualitative and quantitative analysis. In this paper, an exhaustive review of recent related wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 121 publications
0
20
0
Order By: Relevance
“…The application of machine learning techniques in THz imaging and sensing have been extensively reviewed in [181], [182], [183], [184], [185], [186], [187] and [188]. However, most of the machine learning models that have been explored in THz imaging and sensing for biomedical applications are based on shallow networks due to the unavailability of sufficient training datasets.…”
Section: B Artificial Intelligence and Robotics In Thz Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…The application of machine learning techniques in THz imaging and sensing have been extensively reviewed in [181], [182], [183], [184], [185], [186], [187] and [188]. However, most of the machine learning models that have been explored in THz imaging and sensing for biomedical applications are based on shallow networks due to the unavailability of sufficient training datasets.…”
Section: B Artificial Intelligence and Robotics In Thz Healthcarementioning
confidence: 99%
“…Machine learning techniques in THz imaging and spectroscopy are useful for data pre-processing, qualitative and quantitative multivariate data analysis and other tasks like compressive sensing, image super resolution and image reconstruction etc. [181].…”
Section: ) Challenges In Data Driven Thz Studiesmentioning
confidence: 99%
“…Both the high information content and high noise levels of tradiutional THz spectra logically naturally lead to the application of machine learning (ML) for their analysis. The recent advances in this area showed that THz spectra can be accurately and automatically decoded with highly trained ML algorithms even when peaks are broad and often indistinct. These capabilities become particularly important in biomedical fields, where chemometric ML models in data preprocessing, feature selection, and multivariate analysis improve the accuracy of disease diagnosis. …”
Section: Future Directionsmentioning
confidence: 99%
“…Terahertz (THz) time-domain spectroscopy (TDS) has become a unique technique in the fields of material characterization [1][2][3], biomedicine [4,5], and information technology [6]. Therefore, the development of THz technology directly affects the applications of advanced science.…”
Section: Introductionmentioning
confidence: 99%